Land readjustment: The missing link in urban Zimbabwe - Charles Chavunduka (African Journal on Land Policy and Geospatial Sciences, 2018)
Zimbabwe has been experiencing a rapid rate of urbanization amidst a failure by conventional approaches of urban land management to cope with the demand for housing. In view of these challenges, this paper investigates the feasibility and nature of land readjustment for urban land management in Zimbabwe. Using case study research methodology and a desk review of evidence from developed and developing countries the potential use of land readjustment in Zimbabwe is examined. Findings from Zimbabwe show the existence of opportunities for use of land readjustment in rationalizing urban land use. However, the study revealed constraints concerning the legal framework, limited public participation in planning, and the complexity of the land readjustment process. Overall, it is the authors’ conclusion that evident opportunities for land readjustment would require legal and institutional reforms providing for the concept in law and the adoption of more inclusive planning methods by urban authorities.